Radiographic progression of hospital referred osteoarthritis of the hip. Issue 4 (April 1993) - Ledingham, J; Dawson, S; Preston, B; Milligan, G; Doherty, M
Abstract : Various factors have been considered important in the rate of progression of osteoarthritis of the hip, though few data are available from large longitudinal studies. One hundred and thirty six patients referred to hospital (85 women, 51 men; mean age 65 years, range 29-86 years) with osteoarthritis of the hip (192 affected hips) were followed up for a median of 27 (range 3-72) months. One hundred and six patients (144 affected hips) were reviewed for a minimum of one year (median 28, range 12-72 months). Fifty three per cent of all osteoarthritic hips required an operation at a median of 14 (range 3-48) months from entry. All radiographs before and after entry were examined (median four films for each patient over a median of three years, range 0.5-19 years). Hips showing rapid radiographic progression on prospective films more often had superior migration, or an atrophic bone response; those with no progression more often had an indeterminate, medial, or axial migration pattern, protrusio or mild osteoarthritis at presentation. A higher occurrence of rapid progression was seen in women, in those of older age at symptom onset, and in hips with a higher Kellgren grade at entry; men more often showed no progression. Age at presentation, body mass index, symptom duration, or presence of chondrocalcinosis, hand osteoarthritis/nodes, or Forestier's disease did not influence progression. This study supports the contention that, at the time of hospital referral, certain patient characteristics and radiographic features at the hip may help to identify those at high risk of rapidly progressive hip osteoarthritis.